Dramatic effects of speech task on motor and linguistic planning in severely dysfluent parkinsonian speech. - Van Lancker Sidtis, Diana; Cameron, Krista; Sidtis, John J. (Clinical Linguistics & Phonetics, 2012)
In motor speech disorders, dysarthric features impacting intelligibility, articulation, fluency and voice emerge more saliently in conversation than in repetition, reading or singing. A role of the basal ganglia in these task discrepancies has been identified. Further, more recent studies of naturalistic speech in basal ganglia dysfunction have revealed that formulaic language is more impaired than novel language. This descriptive study extends these observations to a case of severely dysfluent dysarthria due to a parkinsonian syndrome. Dysfluencies were quantified and compared for conversation, two forms of repetition, reading, recited speech and singing. Other measures examined phonetic inventories, word forms and formulaic language. Phonetic, syllabic and lexical dysfluencies were more abundant in conversation than in other task conditions. Formulaic expressions in conversation were reduced compared to normal speakers. A proposed explanation supports the notion that the basal ganglia contribute to formulation of internal models for execution of speech.